HGG-17. FOCUSED ULTRASOUND-ENHANCED DELIVERY OF RADIOLABELED AGENTS TO DIFFUSE INTRINSIC PONTINE GLIOMA. (1st June 2021) - Ye, Dezhuang; Zhang, Xiaohui; Yang, Lihua; Yue, Yimei; Tai, Yuan-chuan; Rubin, Joshua B; Liu, Yongjian; Chen, Hong
Abstract: Diffuse intrinsic pontine glioma (DIPG) arising in the brainstem is the deadliest pediatric brain cancer with nearly 100% fatality and a median survival of <1 year. The critical location in the brainstem and the often intact blood-brain barrier (BBB) pose significant challenges in the treatment of DIPG. The objective of this study was to demonstrate the potential for focused ultrasound-induced BBB disruption (FUS-BBBD) to improve DIPG treatment by enhancing the safe and efficient delivery of drugs. A genetically engineered mouse model of DIPG was generated using the RCAS (replication-competent avian sarcoma-leucosis virus long-terminal repeat with splice acceptor)/tumor virus A modeling system. A magnetic resonance-guided FUS (MRgFUS) system was used to induce BBB disruption in these mice with the FUS targeted at the center of the tumor. Two radiolabeled agents with different sizes were used to evaluate the delivery efficiency of the FUS-BBBD technique in DIPG mice: a small-molecular radiotracer, 68 Ga-DOTA-ECL1i, and a radiolabeled nanoparticle, 64 Cu-labeled copper nanoparticles ( 64 Cu-CuNCs, 5 nm in diameter). 68 Ga-DOTA-ECL1i (half-life 1 h) and 64 Cu-CuNCs (half-life 13 h) were intravenously injected into the mice after FUS sonication, and microPET/CT imaging was performed at 1 h and 24 h, respectively, to evaluate the spatial-temporal distribution of these two agents in the brain and quantify the delivery outcome. FUS treatment increased the uptake of 68 Ga-DOTA-ECL1i and 64 Cu-CuNCs to the DIPG tumor by 3.25 folds and 4.07 folds on average, respectively. These findings demonstrated, for the first time, that FUS can increase BBB permeability in a murine model of DIPG and significantly enhance the delivery of agents of different sizes into the DIPG tumor.